Lexical functional grammar - Dalrymple, Mary (Syntax and semantics, 2001)
Volume 34 of "Syntax and Semantics" is a thorough and accessible overview and introduction to Lexical Functional Grammar (LFG), a theory of the content and representation of different aspects of linguistic structure and the relations that hold between them. The book motivates and describes the two syntactic structures of LFG: surface phrasal organization is represented by a context-free phrase structure tree, and more abstract functional syntactic relations like subject and object are represented separately, at functional structure. The book also presents a theory of semantics and the syntax-semantics interface in which the meaning of an utterance is obtained via deduction from semantic premises contributed by its parts. Clear explication of the formal aspects of the theory is provided throughout, and differences between LFG and other linguistic theories are explored. The theory is illustrated by the analysis of a varied set of linguistic phenomena, including modification, control, anaphora, coordination, and long-distance dependencies. Besides its interest to linguists, LFG also has practical applications in computational linguistics and computer science. This book offers thorough overview of the state of the art in Lexical Functional Grammar. It presents clear explanation of the formal tools of the theory. It also offers introduction to the "glue" semantics, a theory of the syntax-semantics interface. It also presents in-depth syntactic and semantic analysis of a variety of linguistic constructions